Assemblies of metal–organic frameworks based on a tetrapodal linker for luminescence sensing of tetrahydrofuran. Issue 16 (29th March 2016) - Gao, Chao-Ying; Wang, Dan; Li, Jian-Ping; Wang, Yuan; Yang, Weiting
Abstract : A high-sensitivity luminescence sensing response to tetrahydrofuran was demonstrated by one MOF based on a rigid silicon-centered tetrahedral ligand. Abstract : The solvothermal assemblies of Zn(ii )/Co(ii )/Ni(ii ) ions and a rigid silicon-centered tetrahedral ligand, tetrakis(3-carboxyphenyl)silicon (H4 L), yield five metal–organic frameworks, formulated as [Zn2 (OH)(dib)0.5 (HL)]·H2 O·2DMF (1 ), Zn3 (OH)2 (phen)2 (H2 L)2 (2 ), [Co2 (OH)(H2 O)3 (DMF)(HL)]·H2 O·2DMF (3 ), [Co2 (OH)(H2 O)(phen)(DMF)(HL)]·H2 O·DMF (4 ) and [Ni2 (OH)(H2 O)2 (DMF)2 (HL)]·H2 O·DMF (5 ) [phen = 1, 10-phenanthroline, dib = 1, 4-di(1 H -imidazol-1-yl)benzene, DMF = N, N -dimethylformamide]. Single crystal X-ray diffraction analyses reveal that1 is a three-dimensional framework structure based on 5-connected [Zn2 (OH)] 3+ secondary building units (SBUs) and the silicon-centred tetrahedral ligands.2 features a one-dimensional architecture constructed from trinuclear [Zn3 (OH)2 (phen)2 ] 4+ SBUs and 2-connected tetracarboxylate ligands. The structures of3–5 are similar, which all contain dinuclear metal-based SBUs linked by 4-connected silicon ligands, resulting in layered sql nets. The syntheses, structures, thermal stabilities and photoluminescence of these compounds are studied. Further luminescence studies reveal that1 exhibits a high-sensitivity sensing response to tetrahydrofuran.